Characteristics of environmental harm in the context of air pollution. - Irwin, J. G.; Duarte-Davidson, Raquel; Pollard, Simon J. T. (WIT Press, 2002)
A framework that allows a qualitative assessment of technical and socio-economic aspects of environmental harm has been developed; capturing not only the physical aspects of damage but also how society may feel about it. Technical characteristics of harm include spatial and temporal extent, severity, irreversibility and uniqueness. Social aspects include dread, distrust, equity and imposition. By representing these on separate axes of a graph it is possible to assess those attributes of greatest concern, draw conclusions as to the nature of the harm and the public perception of that harm and gain some insight into appropriate courses of action. The results of applying the methodology to a radioactive release are presented and placed in the context of a range of other air pollution hazards.